Origin How did life on Earth begin? - Illustra Media (Firm) ([Murrieta, Califonia] : Illustra Media, 2016)
In 2002, Illustra Media released Unlocking the Mystery of Life. This remarkable documentary challenged the paradigm of scientific materialism and the belief that life is nothing more than the product of blind, undirected processes. Unlocking's influence was global, and now its impact continues through the film's long-awaited sequel, Origin: Design, Chance and the First Life on Earth. With spectacular computer animation, Origin examines a question that has baffled science for centuries: How did life on Earth begin? Today, most researchers insist it arose through simple chemistry that transformed inanimate matter into the first living cell. Yet, this explanation is devoid of evidence and unsatisfying, even to its most ardent supporters. As Origin exposes the flaws of materialistic theories, you'll travel through a molecular universe filled with extraordinary biological engineering fundamental to every organism that has ever existed. Engineering that points clearly to intelligence and mind. Origin transcends science to touch the heart and mind of anyone who has ever pondered the deepest mystery of the human experience: Where did we come from and why are we here? - Container.
With spectacular computer animation and cutting-edge research, "Origin" examines a question that baffled science for centuries: How did life on Earth begin? Today, most researchers insist it arose through simple chemistry that - without direction or plan - transformed inanimate matter into the first living cell. Yet, this explanation is devoid of evidence and unsatisfying, even to its most ardent supporters. As "Origin" exposes the flaws of materialistic theories, you will travel through a molecular universe to encounter extraordinary biological engineering fundamental to the survival of every organism that has ever existed. Engineering that points clearly to intelligence and mind.
First life -- How to build a cell -- Life from non-living matter -- Chance and probability -- Amoeba's journey -- Materialism and design.
Title from title screen.
DVD video.
105772
Keywords: Creationism; Life -- Origin; Evolution (Biology); Molecular evolution; Intelligent design (Teleology); Documentary films; Educational films; Nonfiction films